A 'Second Edition' of Keynes's General Theory - Anthony Philip Thirlwall (University of Kent, Department of Economics, 1998)
This is a review article of A 'Second Edition' of the General Theory Vols 1 and 2 edited by G.C. Harcourt and P.A. Riach (London: Routledge, 1997).
Keywords: E12; B3; 330; Keynes; Keynesian Economics; Post-Keynesian Economics; Wirtschaftstheorie; Großbritannien